Asabiyyah, religion and regime types: re-reading Ibn Khaldun - Ra'ees, Wahabuddin (IIUM Press, International Islamic University Malaysia, 2004)
Ibn Khaldūn found a “causal determinative analytical tool” to explain development, progression and disintegration of ‘umrān (lit. culture). He argued that ‘umrān comes into existence as a result of five types of causes: (1) the “ultimate or first cause,” (2) final cause, (3) efficient cause, (4) formal cause, and (5) material cause. However, in Ibn Khaldūn’s scheme of analysis, the efficient cause of ‘umrān and political institutions consists of two factors: (1) ‘aṣabiyyah and (2) religion. Ibn Khaldūn believed that a meaningful investigation of the relationship between religion, ‘aṣabiyyah and ‘umrān is possible if investigation is narrowed down to the study of human nature. Hence, according to Ibn Khaldūn, what is true of human nature is also true of ‘umrān. Stated differently, the rules applicable to human nature are applicable to ‘umrān and political institutions.